PERHITUNGAN WAKTU DAN BIAYA PADA PROSES PEMESINAN BENDA UJI TARIK - Christian Aidy Mosey; Rudy Poeng; Johan S C Neyland (JURNAL POROS TEKNIK MESIN UNSRAT, 2015)
A machine tool must be able to produce high-quality product. But a skilled operator also required. The process of workpiece production begins with planning a logical working steps, such as: specifying the type of machine toolâ€™s process and selecting the materials to be used. The production process is not only related to the technology, but also related toÂ  the cost factor and the production speed to achieve the target and optimum profits. In the tensile test, the specimen is standardized according to the tensile machine that will be used. The shape of the tested specimen is essential in order to avoid cracking or facture in the grip or others areas. The purpose of this study are determining the average time of machining proces and getting the total cost of production of machining process of a tensile test specimen. The tensile test specimen were subjected on this experiment has a circular cross-sectiolan shape which made from concrete steel with the lathe machining proces. Based on the result of the process of time and cost calculation, the tensile test specimens has an average machining time of 161,733 minutes per specimen and the cost Rp. 63.483 per specimen. Keywords: Process time, production cost, the tensile test specimen